Synthesis of porous materials by the modification of coal fly ash and its environmentally friendly use for the removal of heavy metals from wastewater - Hussain, Zawar; Zhang, Hao; Chang, Na; Wang, Haitao (Frontiers in Environmental Science, 2022)
Wastewater is a complex mixture of many pollutants, where the high-risk pollutants are heavy metals (HMs) in industrial wastewater due to its difficult removal. In this study, flocculants particles of modified coal fly ash (MCFA) were prepared by the modification of coal fly ash (CFA) using NaOH-HCl-NaOH method. The morphological structure and elemental composition of the prepared MCFA were analyzed through characterization analysis i.e., SEM, BET, FT-IR, EDX, XPS, and XRD. Results found that the surface area of the flocculant particles of MCFA was increased from 5.241 m2/g to 32.011 m2/g, which increased the adsorption process of HMs (Mn2+, Cu2+, Ni2+ and Pb2+). The maximum removal efficiency (R %) of MCFA for Mn2+, Cu2+, Ni2+ and Pb2+ were recorded 94.26%, 95.88%, 71.04% and 99.91%, respectively. The Freundlich isotherm model was fitted for adsorption process and the maximum adsorption amount of MCFA for Mn2+, Cu2+, Ni2+ and Pb2+ were 558.9219 mg/g, 0.4341 mg/g, 210.9737 mg/g and 12.1957 mg/g Moreover, the kinetic model indicated that physicochemical adsorption was occurred between the adsorbate materials and adsorbent.